Identification of New Rat Bone Marrow-Derived Population of Very Small Stem Cell with Oct-4A and Nanog Expression by Flow Cytometric Platforms - Anna Labedz-Maslowska; Elzbieta Kamycka; Sylwia Bobis-Wozowicz; Zbigniew Madeja; Ewa K. Zuba-Surma (Hindawi Limited, 2016)
Very small embryonic-like stem cells (VSELs) represent a unique rare population of adult stem cells (SCs) sharing several structural, genetic, biochemical, and functional properties with embryonic SCs and have been identified in several adult murine and human tissues. However, rat bone marrow- (BM-) derived SCs closely resembling murine or human VSELs have not been described. Thus, we employed multi-instrumental flow cytometric approach including classical and imaging cytometry and we established that newly identified population of nonhematopoietic cells expressing CD106 (VCAM-I) antigen contains SCs with very small size, expressing markers of pluripotency (Oct-4A and Nanog) on both mRNA and protein levels that indicate VSEL population. Based on our experience in both murine and human VSEL isolation procedures by fluorescence-activated cell sorting (FACS), we also optimized sorting protocol for separation of CD45−/Lin−/CD106+ rat BM-derived VSELs from wild type and eGFP-expressing rats, which are often used as donor animals for cell transplantations in regenerative studies in vivo. Thus, this is a first study identifying multiantigenic phenotype and providing sorting protocols for isolation VSELs from rat BM tissue for further examining of their functional properties in vitro as well as regenerative capacity in distinct in vivo rat models of tissue injury.